Changes in Posttraumatic Brain Edema in Craniectomy-Selective Brain Hypothermia Model Are Associated With Modulation of Aquaporin-4 Level - Szczygielski, Jacek; Glameanu, Cosmin; Müller, Andreas; Klotz, Markus; Sippl, Christoph; Hubertus, Vanessa; Schäfer, Karl-Herbert; Mautes, Angelika E.; Schwerdtfeger, Karsten; Oertel, Joachim (Frontiers in Neurology, 2018)
Both hypothermia and decompressive craniectomy have been considered as a treatment for traumatic brain injury. In previous experiments we established a murine model of decompressive craniectomy and we presented attenuated edema formation due to focal brain cooling. Since edema development is regulated via function of water channel proteins, our hypothesis was that the effects of decompressive craniectomy and of hypothermia are associated with a change in aquaporin-4 (AQP4) concentration. Male CD-1 mice were assigned into following groups (n =5): sham, decompressive craniectomy, trauma, trauma followed by decompressive craniectomy and trauma + decompressive craniectomy followed by focal hypothermia. After 24h, magnetic resonance imaging with volumetric evaluation of edema and contusion were performed, followed by ELISA analysis of AQP4 concentration in brain homogenates. Additional histopathological analysis of AQP4 immunoreactivity has been performed at more remote time point of 28d. Correlation analysis revealed a relationship between AQP4 level and both volume of edema (r2 = 0.45, p < 0.01, **) and contusion (r2 = 0.41, p < 0.01, **) 24h after injury. Aggregated analysis of AQP4 level (mean ± SEM) presented increased AQP4 concentration in animals subjected to trauma and decompressive craniectomy (52.1 ± 5.2 pg/mL, p = 0.01; *), but not to trauma, decompressive craniectomy and hypothermia (45.3 ± 3.6 pg/mL, p > 0.05; ns) as compared with animals subjected to decompressive craniectomy only (32.8 ± 2.4 pg/mL). However, semiquantitative histopathological analysis at remote time point revealed no significant difference in AQP4 immunoreactivity across the experimental groups. This suggests that AQP4 is involved in early stages of brain edema formation after surgical decompression. The protective effect of selective brain cooling may be related to change in AQP4 response after decompressive craniectomy. The therapeutic potential of this interaction should be further explored.